Factors That Affect Profitability of Banks Comparative Study between Indonesian and Hong Kong - Farah Margaretha; Adisty Adisty (KINERJA, 2017)
The problem of this research was the influence of liquidity risk, net credit facilities to total assets ratio, total investment to total assets ratio, total equity to assets ratio, net credit facilities to total deposits ratio, cost to income ratio, and bank size toward return on assets. The objective of this research was to identify the factors that influence return of assets of banks listed in Indonesia Stock Exchange and Hong Kong Stock Exchange over the period 2012-2015. The methodology of this research was multiple linear regression which is tested by using classic assumption. Sample in this research were 27 Banks listed in Indonesia Stock Exchange and 13 Banks listed in Hong Kong Stock Exchange over period 2012-2015. Finding and contribution in this research were liquidity risk, total equity to assets ratio, net credit facilities to total deposits ratio, cost to income ratio, and bank size have influence toward return on assets of banks in Indonesia. Meanwhile, net credit facilities to total assets ratio and total investment to total assets ratio do not have influence toward return on assets of banks in Indonesia. Liquidity risk, total equity to assets ratio, and cost to income ratio have influence toward return on assets of banks in Hong Kong, meanwhile credit facilities to total assets ratio, total investment to total assets ratio, net credit facilities to total deposits ratio, and bank size do not have influence toward return on assets of banks in Hong Kong. Research limitation or implication in this research was for banking management to use the the information to maintain or even increase the profitability of banks, and to investors for being used as considerations to invest in banking sectors.Keywords: profitability, liquidity risk, bank size, investment